Presenting Our Own Narratives: Alan Greyeyes in Conversation with Melody McKiver - McKiver, Melody (Critical Studies in Improvisation / Études critiques en improvisation, 2021)
Alan Greyeyes is Director of the sākihiwē festival, which works to develop audiences for live music among Indigenous youth, and runs the artist and project management company Ogichidaa Arts. In this interview, he speaks with Anishinaabe musician/composer Melody McKiver about the impact of the pandemic on Indigenous musicians and music communities.